The Influence of Juvenile Graves’ Ophthalmopathy on Graves’ Disease Course - Jurate Jankauskiene; Dalia Jarusaitiene (Journal of Ophthalmology)
Purpose. To investigate juvenile Graves’ ophthalmopathy (GO) signs and compare Graves’ disease (GD) course in patients with or without GO. Patients and Methods. There were analyzed data (visual acuity, proptosis, palpebral fissure measurements, clinical activity score (CAS), and the course of GD) of 67 children who have been newly diagnosed with GD. 26.9% of patients with GD had signs of ophthalmopathy (GO+), and 73.1% were without ophthalmopathy (GO−). Results. Upper eyelid retraction (72.3%), proptosis (66.7%), and soft tissue changes (27.8−38.9%) were in GO+ patients. The palpebral fissure, CAS, and proptosis values were greater in the GO+ group than in the GO− group (p<0.001). GD course in GO+ patients was longer than that in GO− patients (p<0.001). The duration of the first remission was longer in GO− than in GO+ patients (p<0.001). The duration of first remission was longer than one year for 61.2% in GO− and 33.3% in GO+ patients (p<0.02). Conclusion. The common manifestations of juvenile GO patients were upper eyelid retraction, proptosis, and soft tissue involvement. The study demonstrates that pediatric patients with GO are more likely to have a severe course of autoimmune thyroid disease.